Modelo de gestión EFQM de la empresa de agua Llanganati del cantón Salcedo. - Porras Ortiz, Edwin Rubén (2021)
This research work proposes to develop an EFQM management model, in the "Llanganati" water bottling company of the Salcedo canton, based on the problems identified, which were lack of leadership by the administration, ignorance of the mission, vision, objectives and strategies, low planning in production, lack of optimization of processes, there are no indicators, there is no evaluation of staff performance and there is no feedback on the degree of customer satisfaction. The research was descriptive, considering the real data of the company, without manipulation, identifying the current situation of the company; the modality was documentary and scientific, with a qualitative-quantitative approach, which allowed determining the productive process in the company, identifying the types of processes and the distribution of personnel; For the diagnosis of the company, the REDER matrix and a questionnaire were applied to a sample of 56 people, thus managing to identify the facilitating agents and the company's results. The EFQM management model, proposed in the Llanganati company, was developed in two phases: Phase I Self-assessment, obtaining customers and society as strong points, with the areas for improvement being leadership, strategy and policies, people, resources and alliances, processes, products and services, results in people and key results; In Phase II, it was determined that the company must implement the following action plans: a quality manual and self-assessment processes, communication process, training process, product and service development process, marketing and marketing process, process for the distribution of personnel and work areas, and a process for the implementation of indicators; concluding that the EFQM model is the opportunity to have an effective management, correctly determine the roles of each employee; the aspects that must be considered when managing resources, making the most of the company's processes, always oriented to the client and to the objectives set.